Analysis on the Development of Fashion Brands under the Concept of Sustainable Fashion - Yu, Qingxi (Transactions on Economics, Business and Management Research, 2024)
In recent years, with the growth of the fashion industry's pollution index, some brands have focused on sustainable development. To solve the problems brought by the fashion industry, this paper uses Stella McCartney as a case study, analyzes the effectiveness of sustainable development from three perspectives, and makes suggestions. The first aspect is environmental protection. Stella McCartney is cruelty-free, develops innovative materials, and promotes the sustainable development of the brand. The second aspect is social responsibility. Stella McCartney prioritizes the respect of human rights and the protection of workers' rights and well-being, thereby exerting a significant influence on the sustainable development of social responsibility. The final aspect is economic viability, with Stella McCartney planning a new textile economy that promotes the development of a circular economy in the fashion industry. Because of these three aspects, this paper puts forward some suggestions. Firstly, fashion brands should utilize recyclable waste clothing and leather goods, ensuring zero cruelty and reducing the pollution caused by material waste. Secondly, they should collaborate with the local government to engage in tree planting activities, thereby protecting ecological diversity. Lastly, by embracing the circular economy, they can comprehensively promote the sustainable development of their brands. This thesis fills a research gap in the field of sustainable fashion development, offers suggestions for brands to develop sustainable fashion, and significantly advances the development of sustainable fashion.